Sifat Fungsional dan Organoleptik Teh Herbal dengan Perbandingan Bubuk Kayu Manis dan Daging Buah Pala - Ambeua, Juan V; Lawalata, Vita N; Tetelepta, Gilian (Universitas Pattimura, 2025)
This study aimed to determine the optimal concentration of cinnamon powder in nutmeg pulp tea based on its chemical composition and organoleptic properties. The experiment was conducted using a completely randomized design with five treatment ratios of cinnamon powder to nutmeg pulp powder (0%:100%, 2%:98%, 4%:96%, 6%:94%, and 8%:92%), each replicated three times. The results showed that the 4%:96% ratio produced the most favorable outcomes, with a water content of 10.61%, phenol content of 6.12 mg/g, and antioxidant activity of 74.06%. Sensory evaluation indicated that this formulation was moderately preferred in terms of taste (3.20), color (3.20), aroma (3.20), and overall acceptance (2.94). In terms of hedonic quality, the tea was characterized by a slight nutmeg taste (3.25), a brownish-yellow color (2.95), and a slight nutmeg aroma (2.95). These findings suggest that incorporating 4% cinnamon powder provides the best balance between chemical quality and consumer acceptability in nutmeg pulp tea.